Visualisierung und ihre Funktionen bei der Notizennahme im KSD 2 1 - Brzozowska, Lucyna (Glottodidactica, 2005)
Taking notes in consecutive interpreting is of eminent significance. It is directly related to the specificity of consecutive interpreting, in the first line to the phase displacing: at first there is a text presented to be translated and afterwards its respective translation is produced. Written texts which are read aloud are more difficult in the reception than spoken texts. Even more difficult are specialized texts. If a specialized written text is presented orally in longer sequences the consecutive interpreter is able to translate it in the proper way only with help of taking notes.